Considerations for flight testing of search and rescue (SAR) innovations - Bennett, Christopher J.; Hodgkinson, Jane; Nixon, Jim (The Institute of Civil Protection and Emergency Management, 2025)
Flight testing of new aircraft, equipment and systems is mandatory in the aviation industry to establish and verify the airworthiness of any new airborne product as determined by the appropriate authority, for example the Federal Aviation Administration (FAA) in the United States or the European Union Aviation Safety Agency (EASA) in Europe. Testing procedures for civilian and military category products are well documented and strictly regulated (see, for example the FAA flight test guide for certification of normal, utility, acrobatic, and commuter category aircraft (FAA, 2011) and often use traditional techniques. However, the are no published guidelines for flight testing new developments in the search and rescue (SAR) domain. This article summarizes, from experience, recommendations for a successful SAR flight test campaign. This includes considerations for effective and efficient trial design, best practices for data capture across a range of environmental conditions, and methods to minimize sources of error. A detailed example of a search procedure with sequential steps is also provided. The principles discussed herein target quality data capture via flight test, both efficiently and safely, to improve and evolve the vital work that SAR operations conduct worldwide.
Keywords: 40 Engineering; 4001 Aerospace Engineering; Flight-Test design; innovations; review; case study